Developmental Trajectories of Regulating Attentional Selection Over Time - Heim, Sabine; Keil, Andreas (Frontiers in Psychology, 2012)
Adaptive behavior in learning environments requires both the maintenance of an attentional focus on a task-set and suppression of distracting stimuli. This may be especially difficult when the competing information is more appealing than the target event. The aptitude to “pay attention” and resist distraction has often been noted as an important prerequisite of successful acquisition of intellectual abilities in children. This focused review draws on research that highlights interindividual differences in the temporal dynamics of attentional engagement and disengagement under competition, and their relation with age and cognitive/academic skills. Although basic strategies of attention control are present in very young children, the more refined ability to manage attentional resources over time in an economic and adaptive fashion appears during early school years, dramatically improves until the early teen years, and continues to develop into late adolescence. Across studies, parameters of attention control over time predict specific aspects of academic performance, rather than general intellectual ability. We conclude that the ability to strategically regulate the dynamic allocation of attention at rapid rates may represent an important element of cognitive and academic development.